(3eSGdc GdCagGe aj TQM TQGFY GdESdGes - (3GdTGej GdYGedj, CHh efUhQ, GHf GdTgjO GdKGfj, GHf GdTgjO GdKGfj, GdMSf Hf Rjf GdOjf Hf Ydj GdTGej GdYGedj, J (B1011(3g` (B1602(3es ((3CMeO Hf eMeO GdcQhfjs)
(3ChdgG (B:s
(3ChdgG(B: (3cJGH GdELGQI, aj GdYbO Ydi KdGK GdefaYI GdeZdhHI (B... (3aGdYbO HefRdI GdLfS jTJed SGFQ GdYbhO hNQL HJYdbg HGdfaYI GdHjY hGdUdMs
(3BNQgG (B:s
(3CNQgG(B: (3CHh LYaQ Yf CejQ GdeDefjf hgh eTcd Ydi GWdGbg aEf eLQO hbhYg CYe ef JaQjYge ajg Hd ef JaQjW GdYGbd hef Ke ChQOgG GdeUfa cZjQg HdaX GdQhGjI hjecf MdgG Ydi eG dh Ybdg hSdeg Edjge aaQWhG Ch fMh Pdc hGdCbhi VeGf GdeaQW efge Ohf ZjQg hGdQhGjI McGjI aj hs
(3efbhdI Yf fSNI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 192s
(3GdPQjYI, L (B20: 246s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis